Al-Quran and Science as Perspectives of Mitigation the Impact Climate Crisis on Indonesian Food Security in Pandemic Corona Virus-19 - Karana Yankumara; Roudlotul Jannah; Nilatul Azizah (Journal Intellectual Sufism Research (JISR), 2022)
. Climate change is a significant change in climate, air temperature, and rainfall over a long period. The climate crisis affects weather patterns, which will then impact planting and harvesting seasons, including for Indonesian farmers. This situation is exacerbated by the pandemic, the Covid-19 outbreak that hit the world in early 2020 has hampered many people's daily activities. Allah through His verses in the Qur'an has provided clear instructions for humans on how to use and protect nature, including disaster management such as the climate crisis and pandemics or disease outbreaks. Through literature review studies, research on the relationship between science and the Koran in disaster management aims to maintain food security so that it is always stable amidst climate crises and pandemic disasters. This study on solutions to the climate crisis, pandemics, and food security uses a qualitative method with a literature review type. This study uses phenomenological analysis and functionalism analysis with a hermeneutic approach. From various studies, it can be concluded that the solution to tackling the impact of the climate crisis on food security in the era of the Covid-19 pandemic from the perspective of the Quran and science includes, firstly, making environmental sustainability, climate change, and food security as a broadcast topic. Second, is the application of sustainable agriculture and food diversification, and third is urban farming.